Ethical principles of complementary medicine application in health tourism - Krstić, Vesna; Živanović, Sandra (Hotel and Tourism Management, 2020)
The subject of the research is the application of certain ethical principles in the implementation of complementary medicine in health tourism from the aspect of medical ethics and business ethics in tourism. The aim of the research is to identify the importance of applying certain ethical principles in the implementation of complementary medicine in health tourism. Bibliographic-speculative and descriptive analytical methods were used. The research showed that the application of all ethical principles contained in the Declaration of Helsinki, the International Medical Code of Ethics and the Global Code of Ethics for Tourism is significant and justified in implementing complementary medicine in health tourism, given the structure of beneficiary tourists and the range of services provided within health tourism. The potentials of complementary medicine in terms of its implementation in the corpus of health tourism are still underutilized in the Republic of Serbia, so they could be the subject of some future research in which the application of ethical principles contained in the mentioned documents would be an integral part of them.